IMPLEMENTASI KEBIJAKAN PEMULIHAN PEMBELAJARAN BERKAITAN DENGAN KONTEN DAN KONTEKS PADA KURIKULUM MERDEKA : (Studi Pada SMA Negeri 3 Malang) - Hafis Baginda Alam (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
This Implementation of Learning Recovery Policies Related to Content and Context in the Merdeka Curriculum (Study at SMA Negeri 3 Malang). The education system in Indonesia has changed significantly due to the learning crisis and emergency caused by the COVID-19 pandemic. During the pandemic, the Government of Indonesia has attempted to implement policies to cover potential learning lags and learning gaps through the Decree of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 262/M/2022 concerning Amendments to the Decree of the Minister of Education, Culture, Research and Technology Number 56/M/2022 Concerning Guidelines for Implementing Curriculum in the Framework of Learning Recovery. This study aims to analyze the implementation of the merdeka curriculum at SMAN 3 Malang which is carried out by measuring the success of implementation using two major variables from Merilee S. Grindle's theory, namely content of policy and context of implementation. This type of research is descriptive using a qualitative approach. The results of the study show that the content of policy variable has fulfilled the aspects of interest that affect it, the type of benefit, the degree of change to be achieved, the program implementer, and the resources used. The context of implementation variable has fulfilled the aspects of power, interests and strategies of the actors involved, the characteristics of the institution and regime in power, the level of compliance and the response from the implementer.